The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1067/mtc.2002.120717
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effects of tranexamic acid in elective thoracic aortic surgery: A prospective, randomized, double-blind, placebo-controlled study

Abstract: In this initial series of patients undergoing thoracic aortic surgery, tranexamic acid appeared effective in reducing perioperative bleeding, with a significant reduction in the need for allogeneic transfusions and without any increased risk of thrombotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 30 publications
4
41
0
2
Order By: Relevance
“…Earlier studies have confirmed the favorable effects of antifibrinolytics, including tranexamic acid, on bleeding tendency in patients undergoing cardiac, major orthopedic, transplantation, and prostate surgeries [5,6]. Of particular interest is the increasing use of tranexamic acid by oral surgeons in the form of mouthwash for dental extractions [7,8] and in the management of epistaxis with hereditary hemorrhagic telangiectasia [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…Earlier studies have confirmed the favorable effects of antifibrinolytics, including tranexamic acid, on bleeding tendency in patients undergoing cardiac, major orthopedic, transplantation, and prostate surgeries [5,6]. Of particular interest is the increasing use of tranexamic acid by oral surgeons in the form of mouthwash for dental extractions [7,8] and in the management of epistaxis with hereditary hemorrhagic telangiectasia [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…Although the usefulness of tranexamic acid for DIC caused by aortic dissection has been reported as an alternative treatment to surgical repair (4, 5) and for preoperative control of bleeding complications (8), few articles have discussed the long-term safety and outcomes with this regimen. Therefore, we believe this report will help further clarify potential treatments for this uncommon disorder.…”
Section: Introductionmentioning
confidence: 99%
“…26 -32 Although the incidence is low, 27-32 a dreadful side effect of this drug is increased risk of thromboembolic effects such as acute myocardial infarction, cerebral embolism, pulmonary embolism, and renal pelvis emboli. 26,27 The dose and duration that were used in this study were lower than those reported in the aforementioned studies. 26 -32 Perhaps because of dietary and genetic difference, incidence of postoperative thromboembolism after major surgery tends to be lower among Eastern Asians than among whites.…”
Section: Discussionmentioning
confidence: 78%